Who, where, what and where to now? A snapshot of publishing patterns in Australian orthopaedic surgery. Issue 12 (15th August 2017) - Croker, Nicholas; Lobo, Abhirup; Croker, Anne; Balogh, Zsolt J.; Dewar, David
Abstract : Background: Development of core research competency is a principle of orthopaedic surgical training in Australia. This paper aims to provide an objective snapshot of publications by Australian orthopaedic trainees and surgeons, to contribute to the discussion on how to identify and build on research capability in the Australian Orthopaedic Association (AOA). Methods: By analysing journals with a journal impact factor >1 from 2009 to 2015, data were gathered to explore scientific journal publications by Australian orthopaedic surgeons and trainees in relation to who are the authors, what they are reporting and where they are publishing. Results: One thousand five hundred and thirty‐nine articles were identified with 134 orthopaedic trainees and 519 surgeons as authors. The publication rate for both trainees and surgeons was just over two in five. The majority of studies were of level three or four evidence (Oxford's Centre for Evidence‐Based Medicine guidelines). Only 5% of trainee papers were published without surgeons' co‐authorship. Eighty‐six percent of papers published by surgeons did not involve a trainee. The rates of trainees publishing with other trainees were low. Conclusion: Only 5% of trainee papers were published without surgeons' co‐authorship, highlighting the importance of surgeon mentorship in developing trainee research capability. The 86% of papers published by surgeons without trainee co‐authorship raises the question of missed mentoring opportunities. Low rates of trainee co‐authorship highlight potential for trainees to work together to support each other's research efforts. There is scope for more studies involving higher levels of evidence. This paper raises discussion points and areas for further exploration in relation to AOA trainee research capability.